2006
DOI: 10.1161/01.res.0000199296.70534.7c
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Mutation-Linked Defects in Ryanodine Receptor Autoregulation Reveal a Novel Mechanism of Ca 2+ Release Channel Dysfunction

Abstract: Abstract-Arrhythmogenic cardiac ryanodine receptor (RyR2) mutations are associated with stress-induced malignant tachycardia, frequently leading to sudden cardiac death (SCD). The causative mechanisms of RyR2 Ca 2ϩ release dysregulation are complex and remain controversial. We investigated the functional impact of clinically-severe RyR2 mutations occurring in the central domain, and the C-terminal I domain, a key locus of RyR2 autoregulation, on interdomain interactions and Ca 2ϩ release in living cells. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 40 publications
3
68
0
Order By: Relevance
“…Indeed, recent in vitro experiments suggest that RYR2 mutation location may direct the mode of calcium release dysfunction and accompanying channel instability and that mutations in the C-terminal channel-forming domain may lead to more postactivation channel instability. 26 Larger multicenter studies are needed to validate this association between mutation location and disease severity. In particular, analyzing whether mutation location could play a role …”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Indeed, recent in vitro experiments suggest that RYR2 mutation location may direct the mode of calcium release dysfunction and accompanying channel instability and that mutations in the C-terminal channel-forming domain may lead to more postactivation channel instability. 26 Larger multicenter studies are needed to validate this association between mutation location and disease severity. In particular, analyzing whether mutation location could play a role …”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…However, some RyR2 mutants displayed an increased sensitivity to cytosolic Ca 2+ and caffeine. This is the case for S2246L, N4104K and R4497C mutations expressed in HEK293 cells or HL-1 cells, where it was also shown a gain-of-function RyR2 activity, while there was no change in SR Ca 2+ load (George CH., 2006). In some cases, differences in RyR2 mutants' response to agonists are closely dependent on the mutational locus.…”
Section: Functional Alterations Of Cpvt Related Mutations In the Ryrmentioning
confidence: 93%
“…The central domain (domain II: amino acids 2246-2534) contains an FKBP12.6 binding domain and it is supposed to interact with the Nterminus domain (zipping-unzipping). The C-terminus domain (domain III: amino acids 3778-4201 and domain IV: amino acids 4497 to 4959) contains the transmembrane regions of the Ca 2+ channel and an hydrophobic region which it is postulated to transduce cytoplasmic events to regulate the Ca 2+ pore forming domain (George CH., 2006). Only a small number of mutations are located in regions of RyR2 outside these portions.…”
Section: Ryr2 Mutations In Cpvtmentioning
confidence: 99%
“…Indeed, Yano et al demonstrated correction of interdoamin interaction, associated with reduced Ca leak using the small molecule antioxidant (Edaravone) (57). Changes in interdomain interaction may underly several of the previously suggested mechanisms altering RyR function and may represent another autoregulatory mechanism disturbed in pathological RyR Ca release (13).…”
Section: Calcium In Cardiac Excitationcontraction Couplingmentioning
confidence: 99%
“…Indeed, action on RyR require FKBP12.6. However, whether adding back FKBP12.6 either via overexpression or small molecules represents a future tool to treat CPVT mutations regardless of their position in the large RyR protein remains to be elucidated (13). Another approach in modulating the RyR function focuses on conformational changes.…”
Section: Calcium In Cardiac Excitationcontraction Couplingmentioning
confidence: 99%